Analysis of Liquid Smoke Grade Characteristics from Coconut Shells and Palm Kernel Shell Waste Through a Slow Pyrolysis Process - Afrah, Bazlina Dawami; Riady, M. Ihsan; Payomthip, Panida; Ramadhanty, Rizky Vasya; Rizki, Fadhilah; Alfayyadh, Muhammad Luthfi (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
This research was motivated by the abundance of biomass plantations in Indonesia. Accumulated biomass waste will cause environmental problems. Biomass processing can resolve this issue, by producing functionally and economically valuable products. The purpose of this research was to increase the value of biomass by processing it as liquid smoke through pyrolysis and then proceeding to the purification stage. The purification method applied in this research was a combination of distillation and adsorption processes using natural zeolite. The variables of this research were: two types of biomass, namely coconut shells and palm kernel shells, and liquid smoke grade variations. The analysis parameters were: pH, viscosity, density, acid content, and phenol analysis as well as GC-MS. The characteristics analysis results showed that all liquid smoke samples met the Japanese liquid smoke standard. Based on pH, acid, and phenol analysis, the liquid smoke from the coconut shells sample had better quality compared to the liquid smoke from palm kernel shells, namely with pH 2.36, acid content 0.26 mg/mL, and phenol 2,368.75 ppm. The GC-MS test results indicated that grade-1 liquid smoke from both samples contained antibacterial compounds, such as phosphonic acid, formic acid, and carbamic acid, which have the potential to inhibit bacterial growth.